Dynamics of epidemiological indicators of glaucoma in the Republic of Bashkortostan for the period of 2010–2016 - M.M. Bikbov; A.E. Babushkin; I.I. Khusnitdinov; L. Kh. Murova; E.N. Matyukhina (РМЖ "Клиническая офтальмология")
M.M. Bikbov, A.E. Babushkin, I.I. Khusnitdinov, L. Kh. Murova, E.N. Matyukhina Ufa Eye Research Institute of the Academy of Sciences, Ufa, Russian Federation Aim: to study the main epidemiological characteristics of glaucoma in the Republic of Bashkortostan (RB) over 2016 compared to 2010. Patients and Methods: studies were conducted on the basis of data from the annual statistical reports of ophthalmologists of cities and districts of the RB, as well as of the Ufa Eye Research Institute of the Academy of Sciences and the “Main Bureau of Socio-Medical Expertising on the Republic of Bashkortostan”. Results: in the RB in 2016, at regular medical check-up with glaucoma, 30 508 people were recorded (with POAG — 81.4%), of which 74.9% of patients were over the age of 60, and 75.2% had stage I–II of the disease. The rate of patients with suspected glaucoma was 1.3%, with the diagnosis already established — 0.6%, and in the vast majority of cases (82.8%), these patients had stage I or II.  By 2016, an increase in the rate of patients (by 24.3%) registered at regular medical check-up, in the prevalence (46.8%) and the incidence (35.6%) of POAG was recorded against the background of a decrease in the number of people with primary disabilities due to glaucoma (from 346 to 242). Conclusion: comparative analysis over 2010 and 2016 showed that in the RB over the seven specified years, the number of patients with glaucoma increased from 24,536 to 30,508 people, while the prevalence and incidence of the most frequently diagnosed POAG increased from 114.6 to 168.3 and from 12.9 to 17.5, respectively (per 10 thousand of population in people over 40). The absolute number of people with primary disabilities with glaucoma was reduced due to high coverage of the population with annual preventive examinations with an increasing number of identified patients suspected of having this disease (6304 vs. 7685) and its primary detection at the initial stages, an increase of antiglaucoma operations (including those performed using drains and non-penetrating technology), a broader purpose and use of modern and effective anti-hypertensive drops, first of all, prostaglandins (2 times) and fixed combinations (1.5 times). In the course of conducted analysis, there was a decrease in patients, who underwent surgical treatment (from 27.9% to 23.7%), blind in one and both eyes (from 17.3% to 12.6%). Besides, a tendency to an increase among the patients with glaucoma in the caliber of women (from 56.1% to 63.8%) and those under 60 years of age (from 23.2% to 25.9%) was established. Key words: glaucoma, Republic of Bashkortostan, epidemiological indicators, primary open-angle glaucoma, prevalence, morbidity, primary disability. For citation: Bikbov M.M., Babushkin A.E., Khusnitdinov I.I. et al. Dynamics of epidemiological indicators of glaucoma in the Republic of Bashkortostan for the period of 2010–2016. RMJ “Clinical ophthalmology”. 2018;4:163–167.